Performance Tracking of Thailand's Energy Management System under Energy Conservation Promotion Act - Wongkot Wongsapai (2018)
© 2016 The Authors. Published by Elsevier Ltd. The Energy Conservation and Promotion Act B.E.2535 has promulgated in Thailand since 1992 and have internalized the energy management system (EnMS) concept by issuing the ministerial regulation since 2010. This paper analyses the role, legal framework, and results of country-wide implementing of this regulation. The compulsory scheme EnMS, simplified from ISO 50001 standard, consists of eight-step guideline and aimed to introduce energy management to be the major tool for energy conservation. The EnMS is systematically approach and requires the strong role and commitment from top management along with participation form all levels. We found that around 85% of 8,390 designated facilities submitted their EnMS report in 2014. The estimated energy savings by using ODEX estimation in the year 2013 comparing to the base year 2010 are 179.97 ktoe in selected designated factories and 54.41 ktoe in selected designated commercial buildings. The barriers to implementing the EnMS are also raised.